Hukum Bernilai Pancasila Menentukan Tatanan Pemersatu Elemen Kesatuan Bangsa - Azmi, Azmi (Faculty of Law, Universitas Pasundan, 2025)
Indonesia is currently facing a variety of legal challenges, societal tensions, and crises amid its national diversity. If these issues are not properly and fundamentally addressed, they may evolve into multidimensional crises, leaving behind deep social residues and conflicts in an already uncertain national context. In confronting these problems, a fundamental question arises: can a legal system grounded in Pancasila values provide direction, purpose, solutions, and legal certainty to resolve national issues and strengthen the unity of the nation in pursuit of the ideals of a Rechtsstaat (rule of law state) based on Pancasila and the 1945 Constitution. Using a normative juridical research method supported by secondary data, this study adopts a conceptual–exploratory approach and an inductive qualitative analysis. The findings reveal that law infused with Pancasila values establishes an orderly legal framework with a strong guarantee of effectiveness in resolving societal problems and reinforcing national unity. It concludes that law embodying the substantive values of Pancasila is fundamental, responsive, and accommodative, forming an essential part of the state’s normative order that functions to resolve issues and unite the diverse elements of Indonesian society sustainably, in support of national progress. It is therefore recommended that the values of Pancasila’s five principles be continually integrated into the substance of national legal products to ensure the sustainable resolution of Indonesia’s societal and national challenges.